Utilization of Kahoot Media in Islamic Religious Education Learning to Support Student Learning Concentration at SMAN 1 Sekampung Udik - Muhammad Rino Rimbawan; Irhamudin Irhamudin; M Sayyidul Abrori (Journal of Research in Islamic Education, 2026)
This study aims to analyze the use of Kahoot as a learning medium in improving student learning concentration in Islamic Religious Education subjects at SMAN 1 Sekampung Udik. The background of this study is the low concentration of students' learning caused by monotonous and less interactive learning. This study uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation, with teachers and students as research subjects. The results show that the use of Kahoot is able to increase student focus, participation, and enthusiasm in the learning process. In addition, Kahoot also reduces learning boredom by creating a more interactive and interesting classroom atmosphere. However, this study found several obstacles, such as limited internet connection and learning time management. Thus, Kahoot can be assessed as an effective learning medium in supporting the improvement of student learning concentration in Islamic Religious Education subjects.